HIV Genotypes and Primary Drug Resistance Among HIV-Seropositive Blood Donors in Brazil: Role of Infected Blood Donors as Sentinel Populations for Molecular Surveillance of HIV - Alencar, Cecilia Salete [UNIFESP] (2013)
Background: There are few surveillance studies analyzing genotypes or primary (transmitted) drug resistance in HIV-infected blood donors in Brazil. The aim of this study was to characterize patterns of HIV genotypes and primary resistance among HIV-seropositive donors identified at 4 geographically dispersed blood centers in Brazil.Methods: All HIV-infected donors who returned for counseling at the 4 REDS-II Hemocenters in Brazil from January 2007 to March 2011 were invited to participate in a case-control study involving a questionnaire on risk factors. Viral sequencing was also offered to positive cases to assign genotypes and to detect and characterize primary resistance to reverse transcriptase and protease inhibitors according to World Health Organization guidelines.Results: Of the 341 HIV-seropositive donors who consented to participate in the risk factor and genetics study, pol sequences were obtained for 331 (97%). Clade B was predominant (76%) followed by F (15%) and C (5%). Primary resistance was present in 36 [12.2%, 95% confidence interval (CI) 8.2 to 15.5] of the 303 individuals not exposed to antiretroviral therapy, varying from 8.2% (95% CI: 2.7 to 13.6) in Recife to 19.4% in Sao Paulo (95% CI: 9.5 to 29.2); there were no significant correlations with other demographics or risk factors.Conclusions: Although subtype B remains the most prevalent genotype in all 4 areas, increasing rates of subtype C in Sao Paulo and F in Recife were documented relative to earlier reports. Transmitted drug resistance was relatively frequent, particularly in the city of Sao Paulo which showed an increase compared with previous HIV-seropositive donor data from 10 years ago.